2020
DOI: 10.1186/s13071-020-04428-0
|View full text |Cite
|
Sign up to set email alerts
|

Microfilaria-dependent thoracic pathology associated with eosinophilic and fibrotic polyps in filaria-infected rodents

Abstract: Background Pulmonary manifestations are regularly reported in both human and animal filariasis. In human filariasis, the main known lung manifestations are the tropical pulmonary eosinophilia syndrome. Its duration and severity are correlated with the presence of microfilariae. Litomosoides sigmodontis is a filarial parasite residing in the pleural cavity of rodents. This model is widely used to understand the immune mechanisms that are established during infection and for the screening of ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 81 publications
(103 reference statements)
3
17
0
Order By: Relevance
“…We recently described pathology of the visceral pleura (on the surface of the lung) in microfilaremic mice and gerbils (results from ( 12 , 44 ) summarized in Supplementary Table 1 ). In the current study, electron microscopy of the costal parietal pleura showed a smooth appearance in naive mice ( Figures 2A, B ) while the parietal pleura of infected WT mice revealed a strong inflammatory reaction with a high density of polyps ( Figures 2C, D ) of similar aspect to those observed in gerbils ( 44 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently described pathology of the visceral pleura (on the surface of the lung) in microfilaremic mice and gerbils (results from ( 12 , 44 ) summarized in Supplementary Table 1 ). In the current study, electron microscopy of the costal parietal pleura showed a smooth appearance in naive mice ( Figures 2A, B ) while the parietal pleura of infected WT mice revealed a strong inflammatory reaction with a high density of polyps ( Figures 2C, D ) of similar aspect to those observed in gerbils ( 44 ).…”
Section: Resultsmentioning
confidence: 99%
“…We recently described pathology of the visceral pleura (on the surface of the lung) in microfilaremic mice and gerbils (results from ( 12 , 44 ) summarized in Supplementary Table 1 ). In the current study, electron microscopy of the costal parietal pleura showed a smooth appearance in naive mice ( Figures 2A, B ) while the parietal pleura of infected WT mice revealed a strong inflammatory reaction with a high density of polyps ( Figures 2C, D ) of similar aspect to those observed in gerbils ( 44 ). These polyps were mainly observed along the intercostal space, at the edge of the ribs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were then cleared for 45 minutes using Ce3D clearing solution prepared as described 51 and slices were transferred to glass slides, covered with Ce3D and coverslipped. Tiled images were acquired with a Zeiss LSM 880 NLO multiphoton microscope (Carl Zeiss, Germany) equipped with a 32-channel Gallium Arsenide Phosphide (GaAsP) spectral detector (Carl Zeiss, Germany) using 20×/1 NA water immersion objective lens as previously described 69 . Samples were either excited with a tunable pulsed laser in multiphoton mode (Discovery, Coherent, USA) set at 1000 nm, or with the combination of 405, 488 and 633 continuous wave lasers for single-photon operation.…”
Section: Fluorescence Imaging Of Cleared Liver Samplesmentioning
confidence: 99%
“…The presence of MF in particular has a significant impact on inflammation in the lung and pleural cavity. Recent studies by Fercoq et al ( 2020 ) demonstrated the formation of polyps on the pleura that consisted of up to 60% immune cells. The formation of these polyps which consisted mainly of CD3+ lymphocytes, CD68+ macrophages, and eosinophils correlated with the MF load (Fercoq et al 2020 ).…”
Section: Human Filarial Speciesmentioning
confidence: 99%